(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
The analyzes of the symbolic meaning of food, the culinary habits and the behavior at the table were stimulated by the New Cultural History and favored the studies on the relations between food, culture and social structure. Thus, in this article we intend to discuss the Mesopotamian banquet, its sacred roots, the myths of food creation, the material culture and the rich iconography on the subject.